Health Monitoring of Plate Structures Using Ultrasonics - Arjun, S. (My University, 2009)
Health monitoring for damage detection utilizing ultrasonic waves is an emerging field. It uses transmission of high frequency sound waves into a material to detect imperfections, damages or to locate changes in material properties. The most commonly used ultrasonic testing technique is pulse echo wherein sound is introduced into a test object and reflections (echoes) are returned to a receiver from internal imperfections. It is assisted by pulse transmission to quantify the magnitude of damages. This report presents the use of above two techniques to detect the damage in steel plates with manufactured defects in the form of holes, punches, notches. The exact location of damage is known by pulse echo and through transmission is used to know the magnitude of damage in plates. Negative spike pulse is used as an input signal to sending transducer through Pulser/Receiver system and transmitted pulse is received at the other end by receiving transducer. Testing of plates in air is done by placing the transducer in direct contact with plate where the wave travels through the plate from the transducer with the help of couplant (ultrasonic gel). Due to some problem faced in damage detection while testing the plates in air, testing of plates is done by keeping the plate in water where the plate is surrounded by water. Ultrasonic waves are introduced at different angles in the subject specimen in both pulse echo and through transmission technique. The wave signatures obtained are analysed using digitizer card. A parametric study is carried out to see the effect of change in location of damage and magnitude of damage on wave propagation through steel plates for a particular type of damage. The final results obtained were reported in the form of voltage-time curves. For different damage types, most ideal modes were selected. Modes of different frequencies were generated and found the best mode for the testing of various defects on different plate thickness.
M.E. (CAD/CAM and Robotics)
Keywords: Ultrasonics, Health Monitoring, Pulse Echo, Through Transmission, Tomograms